BIOPHILIC ARCHITECTURE AS AN APPROACH TO DESIGN BELAWAN STATION - Novrial; Riry Awinda Sari (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Railways represent a significant mode of mass public transportation, capable of facilitating the movement of passengers and goods on a substantial scale. In light of the observed surge in passenger and freight traffic at Belawan Port, it is imperative to undertake an upgrade to the Belawan railway station. This enhancement is not only driven by the current demand but also serves for the developments of national railway network, which is scheduled until the year 2030. As a cultural heritage building, it is crucial to meticulously plan its renovation and modernization to ensure that its historical and cultural significance is preserved and enhanced. Given the natural conditions of the area, biophilic architecture was chosen as the design methodology. Biophilic design is an architectural approach that incorporates natural elements into the built environment. Integrating natural elements into buildings can create comfortable, healthy, and sustainable spaces at Belawan Station. Biophilic architecture can be an effective approach in designing railway station that are not only functional, but also environmentally friendly and human-oriented